Evaluation of local spices and herbs as marinating ingredients for the reduction of heterocyclic amines in grilled beef - Sepahpour, Shabnam (2017)
Heterocyclic aromatic amines (HCAs) are an important group of food mutagens and potential carcinogens which are formed during heat processing. Phenolic compounds, ubiquitous in plants are well known for their free radical scavenging activities which can inhibit the formation of HCAs. There is no study which have investigated the effects of different proportions of spices/herbs on the reduction of HCAs in grilled beef. This research has been conducted to determine the antioxidant property of selected herbs and spices, optimize the proportion of their combination to achieve the highest reduction of HCAs, identify the main bioactive inhibitors of HCAs formation and explore the level of mutagenicity and toxicity of marinated grilled beef. Selected herbs and spices (turmeric, curry leaf, lemon grass and torch ginger) were evaluated for their total phenolic compound (TPC), total phenolic content (TFC), DPPH radical scavenging activity and ferric reducing antioxidant power (FRAP). The bioactive compounds of the samples were identified using high performance liquid chromatography (HPLC). Nineteen combinations of selected herbs and spices (turmeric, curry leaf, lemon grass and torch ginger) based on a simplex centroid mixture design were used to marinate beef in order to determine the optimal proportion which achieve the highest reduction of HCAs. The results showed that the combination of turmeric and lemon grass exhibited the highest reduction of HCAs. The optimum mixture of crude extract of these herbs was fractionated to determine the main inhibitors of PhIP formation. Six fractions were collected and applied into PhIP model system containing glucose, phenylalanine and creatinine. Liquid chromatography-mass spectrometry quadruple time of flight (LC-MS/MS Q-TOF) and orthogonal partial least-squares (OPLS) analysis was used to correlate PhIP reduction to different metabolite profiles of each fraction. In vivo and in vitro experiments were respectively carried out using zebrafish embryo and Salmonella Typhimurium (Ames test), to determine whether total HCAs reduction in optimized marinated grilled beef exhibited comparable reduction of toxicity and mutagenicity. The results of experiment showed that turmeric possessed the signifinatly highest TPC (172.10 mgGA/dw), TFC (380.7 mgQE/dw), DPPH antioxidant activity (47.35%) and FRAP (55.79 mgQE/gdw basis) which was followed by curry leaf, torch ginger and lemon grass. The combination of turmeric with lemon grass (50:50 w/w) showed the significanyly highest reduction of total HCAs at 94.7%. Using the response optimizer, the optimal proportion of spices and herbs for reduction of total HCAs was found to be a combination of turmeric:lemon grass with the proportion of 52.42%:47.57%. OPLS results indicated that the fraction 5 exhibited remarkable inhibitory activity in the formation of PhIP. The potential inhibitor compounds in this fraction were identified as luteolin, curcumin, luteolin 6-C-Glucosyl (Isoorientin), luteolin 6-CPentosyl- 8-C-pentosyl, Pentosyl-8-C-deoxyhexosyl luteolin, apigenin 7-rutinoside, 2''-O-Rhamnosyl isoorientin, Embigenin 2″-(2″-acetylrhamnoside), apigenin 7- rutinoside-4'-glucoside, luteoin 7-(6″″-acetylollosyl-(1->3)-glucosyl-(1->2)glucoside, Kaempferol 3-rutinoside-7-sophoroside. The results of experiment also showed that the mixture of turmeric and lemon grass (52.42%:47.57%) can be used in the diet of zebrafish without any detrimental effect on liver, kidney, fertility, growth rate and marinades decreased the mutagenic activity in the marinated grilled samples compared with those of the unmarinated samples. The results of the mutagenic activity demonstrated that this optimized marinade formula significantly (p < 0.05) diminished mutagenicity of grilled beef in bacterial Ames test. It can be concluded that all selected herbs and spices utilized in this study possess antioxidant activity which can reduce total HCAs concentration in grilled beef. It is evidenced that combination of turmeric and lemon grass (52.42%:47.57%) gave satisfactory results for the maximum reduction of total HCAs and mutagenicity without any detrimental effect on zebrafish embryo.